P316 TRANSTHYRETIN CARDIAC AMYLOIDOSIS IN PATIENTS WITH SEVERE AORTIC STENOSIS UNDERGOING TRANSCATHETER AORTIC VALVE REPLACEMENT: A SINGLE CENTER EXPERIENCE. (18th May 2022) - Gallone, G; Bongiovanni, F; Bruno, F; Scudeler, L; Landra, F; Andreis, A; Casoni, R; Fava, A; Pidello, S; Raineri, C; Usmiani, T; Alunni, G; et al.
Abstract: Background: Even if prevalent among patients with severe aortic stenosis (AS), the clinical suspicion for transthyretin cardiac amyloidosis (ATTR–CA) remains difficult in this subset. Methods: Consecutive severe AS patients undergoing transcatheter aortic valve replacement (TAVR) evaluation at a single center were prospectively included. Those with suspected ATTR–CA based on clinical assessment underwent 99mTc–DPD cardiac scintigraphy. The RAISE score, a novel screening tool with high sensitivity for ATTR–CA in AS, was retrospectively calculated to rule–out ATTR–CA in the remaining patients. Patients were categorized as follow: "ATTR–CA +": patients with confirmed ATTR–CA at 99mTc–DPD cardiac scintigraphy; "ATTR–CA –": patients with negative 99mTc–DPD cardiac scintigraphy or a negative RAISE score; c) "ATTR–CA indeterminate": patients not undergoing ATTR–CA assessment with a positive RAISE score. The characteristics and outcomes of ATTR–CA + and ATTR–CA – patients were compared. Results: Of 107 included patients, ATTR–CA suspicion was posed in 13 patients and confirmed in 6. Patients were categorized as follow: 6 (5.6%) ATTR–CA +, 79 (73.8%) ATTR–CA –, 22 (20.6%) ATTR–CA indeterminate. Excluding ATTR–CA indeterminate patients, the prevalence of ATTR–CA was 7.1%. As compared to ATTR–CA – patients, ATTR–CA + patients were older, had higher procedural risk and more extensive myocardial and renal damage. They had higher left ventricle mass index and lower ECG voltages, translating into a lower voltage to mass ratio. Moreover, bifascicular block was more common. No difference in procedural outcomes and 1–year mortality was observed between groups. Conclusions: Among severe AS patients, ATTR–CA is prevalent and presents with phenotypic features that may aid to differentiate it from lone AS. The procedural and mid–term outcomes following TAVR seems unaffected by ATTR–CA status.